Pulmonary Alveolar Microlithiasis: CT and pathologic findings in 10 patients - Sumikawa, H.; Johkoh, T.; Tomiyama, N.; Hamada, S.; Koyama, M.; Tsubamoto, M.; Murai, S.; Inoue, A.; Nakamura, H.; Tachibana, T.; et al. (Monaldi Archives for Chest Disease, 2005)
Background and Aim. To evaluate CT findings of pulmonary alveolar microlithiasis and correlate the CT with the pathologic findings. Methods. The study included 10 patients with pathologically proven microlithiasis. Two independent observers evaluated the presence, extent and distribution of the CT findings. CT findings were compared with those at autopsy in two patients and with transbronchial biopsy in eight patients. Results. All patients had a myriad of calcified nodules measuring approximately 1 mm in diameter. Close apposition of the nodules resulted in areas of ground-glass attenuation and consolidation, which were the predominant abnormality on CT in all 10 patients, involving 41% ± 16.3 (mean ± SD) and 30% ± 4.8 of the lung parenchyma, respectively. Calcifications were also seen along interlobular septa, bronchovascular bundles and pleura. Other findings included interlobular septal thickening, thickening of bronchovascular bundles, nodules, and subpleural cysts. There was a solid agreement between the observers for the presence (kappa value; 0.77) and extent (Spearman rank correlation; r= 0.81 to 1.0 p<0.01) of abnormalities. Autopsy specimens demonstrated microliths in alveolar airspaces and along interlobular septa, bronchovascular bundles and pleura. Subpleural small cysts were shown to represent dilated alveolar ducts. Conclusion. Pulmonary microlithiasis is characterised by the presence of numerous small, calcified nodules, calcifications along interlobular septa, bronchovascular bundles and pleura, ground-glass opacities, consolidation, and subpleural cysts. The cysts represent dilated alveolar ducts.